2013
DOI: 10.1177/0218492312466861
|View full text |Cite
|
Sign up to set email alerts
|

Wedge resection verses lobectomy for stage 1 non-small-cell lung cancer

Abstract: Cox regression analysis, neuronal network analysis, and propensity matching in stage 1 non-small-cell lung cancer demonstrate no difference in long-term survival after wedge resection compared to lobectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In addition, recent study by Luzzi’s [19] et al reported sub-lobar resection is followed with a significantly lower five-year survival compared with lobectomy (63% vs. 90%). However, these results may be obscured by comorbid illnesses such as COPD, diabetes and coronary artery disease, which are often present in elderly diagnosed with NSCLC [20, 21]. The choice between sub-lobar resection versus lobectomy is influenced by the surgeon’s and each institution’s experience and preference.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent study by Luzzi’s [19] et al reported sub-lobar resection is followed with a significantly lower five-year survival compared with lobectomy (63% vs. 90%). However, these results may be obscured by comorbid illnesses such as COPD, diabetes and coronary artery disease, which are often present in elderly diagnosed with NSCLC [20, 21]. The choice between sub-lobar resection versus lobectomy is influenced by the surgeon’s and each institution’s experience and preference.…”
Section: Discussionmentioning
confidence: 99%
“…Despite surgery for early stage non-small cell lung cancer (NSCLC) and lung metastasectomy has good tumor control rate, many people are inoperable [31]. As our acknowledgment, midterm results of percutaneous cryoablation (PC) for pulmonary malignancy are limited in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Of the included articles for quantitative analysis, one study was a randomized controlled trial [3], three were propensity-matched comparative studies [36,52,58], and the remaining 50 studies were observational reports. In total, 11 studies were completed prior to 2000, while in another seven studies the majority of patients were recruited before 2000.…”
Section: Quantity and Quality Of Trialsmentioning
confidence: 99%